Contemporary approach to the diagnosis of malignant pleural effusion - Kaul, V; McCracken, D; Rahman, N; Epelbaum, O (American Thoracic Society, 2019)
Advanced malignancy is a prevalent cause of exudative pleural effusion. The management of malignant pleural effusion (MPE) has been the subject of several recent randomized controlled trials and excellent reviews. Less attention has been focused on another controversial and challenging aspect of MPE: it's diagnosis. Prior to selecting the optimal management strategy, the presence of an MPE must first be correctly identified with an emphasis on minimizing invasiveness and discomfort in a patient afflicted with late-stage cancer. The aim of the present review is to summarize the current knowledge about MPE diagnostics and to propose an algorithm for the diagnosis of MPE in established or suspected malignancy.